Развој на липозомски формулации на кетоконазолот - Поповска, Олга (Технолошко-металуршки факултет, УКИМ, Скопје, 2017)
Ketoconazole is an imidazole antimicotic drug used in the treatment of skin diseases, mostly caused by fungal infections. Restrictions of using ketoconazole are due to its side effects, including skin irritation, hepatoxicity, and nephrotoxicity. The objectives of this doctoral thesis were aimed to develop ketoconazole liposomes and evaluate their physical properties such as efficiency of encapsulation, morphological appereance, ζ-potential, electric conductivity and stability during one month stored at 4 °C and 25 °C. Ketoconazole liposomal formulations, using a thin-film hydration, an ultrasonic, and an injection method were determined in this research. Ketoconazole, cholesterol, and L-α- phosphatidylcholine in a weight ratio of 3.3:1:3.3 w/w/w and 6.67:1:3.33 w/w/w were used in the preparation of multilamellar and small unilamellar vesicles or to obtain large unilamellar vesicles, respectively. The mixture was dissolved either in vegetable oil or in methanol. The highest value for the ketoconazole encapsulation efficiency in large unilamellar vesicles was 70.83%. The values for the ketoconazole encapsulation efficiency in multilamellar and small unilamellar vesicles were 93.77% and 90.03%, respectively. The ζ- potential of the obtained multilamellar, small, and large unilamellar ketoconazole vesicles, using ketoconazole, cholesterol, and L-α-phosphatidylcholine in a weight ratio of 3.3:1:3.3 w/w/w were determined - 27.23, - 27.50, and - 30,21 mV, respectively. The most stable liposomes are those kept at 4 °C in a period of one week after preparation.
Development of the ketoconazole liposomal formulations
Докторска дисертација одбранета во 2017 година на Технолошко-металуршкиот факултет во Скопје, под менторство на проф. д–р Весна Рафајловска.
Keywords: Ketoconazole, lecithin, liposomes, vegetable oil